2009
DOI: 10.1248/bpb.32.497
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of Sulfasalazine Transport by Human ATP-Binding Cassette G2

Abstract: Sulfasalazine is an anti-inflammatory agent used for the treatment of chronic inflammatory bowel diseases and rheumatoid arthritis. It displays low passive permeability and low oral bioavailability. ATP-binding cassette G2 (ABCG2) (breast cancer resistance protein (BCRP), mitoxantrone resistance protein (MXR)), an ATP driven efflux pump present at many important pharmacological barriers, most notably in the apical membrane of enterocytes, brain microcapillary endothelial cells, placenta, as well as in the cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…2B). This absolute stimulation is low relative to positive control nilotinib, consistent with the majority of luciferin being ionized and not able to enter the lipid bilayer and interact with ABCG2, as observed for the organic acid substrate sulfasalazine (21). In contrast, the nonionizable ethyl ester of luciferin produced 2.3-fold stimulation of ABCG2 activity (Fig.…”
Section: Significancesupporting
confidence: 73%
“…2B). This absolute stimulation is low relative to positive control nilotinib, consistent with the majority of luciferin being ionized and not able to enter the lipid bilayer and interact with ABCG2, as observed for the organic acid substrate sulfasalazine (21). In contrast, the nonionizable ethyl ester of luciferin produced 2.3-fold stimulation of ABCG2 activity (Fig.…”
Section: Significancesupporting
confidence: 73%
“…In the kidney, ABCB1 is expressed on the apical membrane and has broad substrate specificity, although substrates are usually hydrophobic and either neutral or cationic (DeGorter et al, 2012). ABCG2 plays a similar role to ABCB1 in drug disposition, is generally expressed in the same tissues, and contributes to renal excretion of some drugs (Kage et al, 2002; Jani et al, 2009; Beery et al, 2011). Unlike, ABCB1, the substrate preference for ABCG2 includes hydrophilic conjugated organic anions, particularly the sulfate forms.…”
Section: Kidney Transportersmentioning
confidence: 99%
“…Compound A was an excellent substrate for both Pgp and BCRP with high passive permeability. Sulfasalazine, a poorly permeable compound (Mahar Doan et al, 2002), has been identified as a BCRP substrate in Caco-2 cells by using the BCRP inhibitor 3- (6-isobutyl-9-methoxy-1,4-dioxo-1,2,3,4,6,7,12,12a-octahydropyrazino(1Ј,2Ј-1,6)pyrido(3,4-b)indol-3-yl)propionic acid tert-butyl ester (KO143) and membrane vesicles expressing BCRP (Jani et al, 2009;Lin et al, 2011). P app values of sulfasalazine across BCRP-MDCK or Bcrp-MDCK cells were low in both directions, similar to those of atenolol, a marker of paracellular diffusion, suggesting that sulfasalazine may not be able to penetrate into cells in the absence of uptake transporters.…”
Section: Discussionmentioning
confidence: 99%